Tri Hita Karana as the foundation for digital game development - Saskara, I Putu Adi (Gelar : Jurnal Seni Budaya, 2024)
This research aims to develop a digital game based on the Tri Hita Karana concept to introduce and instill Balinese cultural values in children. Tri Hita Karana, which includes the harmonious relationship between humans and God (Parahyangan), humans and fellow humans (Pawongan), and humans and nature (Palemahan), is integrated into digital games to teach ethical and moral values. This research uses a qualitative approach with Husserl's phenomenological method, which is designed to explore in-depth information about the feasibility of the Tri Hita Karana concept as a basis for digital game development. Data collection was carried out through in-depth interviews, observation and documentation determined by the purposive sampling method. The research results show that the Tri Hita Karana concept is very relevant and effective as a basis for developing educational digital games. The values contained in Tri Hita Karana can be implemented into game features that encourage players to work together, protect the environment, and develop morality. The game "See Sungai," developed in this research, reflects the three dimensions of Tri Hita Karana, namely Parahyangan, Pawongan, and Palemahan, through various educational and interactive gameplay and narrative elements. It is hoped that the implementation of Tri Hita Karana values in this game can strengthen children's character and increase their awareness of Balinese culture. This research concludes that the development of digital games based on the Tri Hita Karana concept is an innovative solution that can help introduce and preserve Balinese cultural values to the younger generation. These games are not only entertaining but also provide significant educational benefits, making them an effective tool in education and cultural preservation.